Kelayakan Limbah Keong Mas sebagai Bahan Dasar Pembuatan Aksesori Rambut Cocktail Style - Saqina Anggelina Akhyar; Ifa Nurhayati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Golden Snail is a pest organism in the agricultural sector that has the potential to reduce the growth of rice plants. Utilization of Golden Snail waste is still limited and is generally only considered as a residue from pest control, even though this waste has the opportunity to be developed into value-added products through upcycling. This study aims to analyze the feasibility of Golden Snail waste as a basic material for making hair accessories. This study uses descriptive quantitative with product validity tests and preference tests, with a one-shot case study design on three types of hair accessories in cocktail style arrangements. Data were collected through observation and documentation, then analyzed using descriptive percentage techniques. The results of the product validity test show that hair accessories made from Golden Snail waste are in the very valid category with an average percentage of 88%, with the highest value in accessory A3 of 90% and the lowest value in accessory A2 of 86%. Meanwhile, the results of the preference test show the very preferred category with an average percentage of 88%, with the highest value in accessory A3 of 90% and the lowest value in accessory A2 of 86%. These findings indicate that golden snail waste has significant potential as an alternative material for making aesthetically pleasing and environmentally friendly hair accessories.